Lymphoid susceptibility to the Aggregatibacter actinomycetemcomitans cytolethal distending toxin (Cdt) is dependent upon baseline levels of the signaling lipid, phosphatidylinositol-3,4,5-triphosphate - Shenker, Bruce J. (Mol Oral Microbiol, 2015)
The Aggregatibactor actinomycetemcomitans cytolethal distending toxin (Cdt) induces G2 arrest and apoptosis in lymphocytes and other cell types. We have shown that the active subunit, CdtB, exhibits phosphatidylinositol-3,4,5-triphosphate (PIP3) phosphatase activity and depletes lymphoid cells of PIP3. Thus we propose that Cdt toxicity results from depletion of this signaling lipid and perturbation of PI-3K/PIP3/Akt signaling. We have now focused on the relationship between cell susceptibility to CdtB and differences in the status of baseline PIP3 levels. Our studies demonstrate that the baseline level of PIP3, and likely the dependence of cells on steady-state activity of the PI-3K signaling pathway for growth and survival, influence cell susceptibility to the toxic effects of Cdt. Jurkat cells with known defects in both PIP3 degradative enzymes, PTEN and SHIP1, not only contain high baseline levels of PIP3, pAkt and pGSK3β, but also exhibit high sensitivity to Cdt. In contrast, HUT78 cells, with no known defects in this pathway contain low levels of PIP3, pAkt and pGSK3β and likely minimal dependence on the PI-3K signaling pathway for growth and survival exhibit reduced susceptibility to Cdt. These differences in susceptibility to Cdt can not be explained by differential toxin binding or internalization of the active subunit. Indeed, we now demonstrate that Jurkat and HUT78 cells bind toxin at comparable levels and internalize relatively equal amounts of CdtB. The relevance of these observations to the mode of action of Cdt and its potential role as a virulence factor is discussed.